Somatoform disorders: time for a new approach in DSM-V. - Mayou, R; Kirmayer, L; Simon, G; Kroenke, K; Sharpe, M (2005)
OBJECTIVE: DSM-III introduced somatoform disorders as a speculative diagnostic category for somatic symptoms "not explained by a general medical condition." Although retained and enlarged in DSM-IV, somatoform disorders have been the subject of continuing criticism by both professionals and patients. The extended period of preparation for DSM-V offers an important opportunity to reconsider the category of somatoform disorders. METHOD: Exploration of the diverse aims of a diagnostic classification indicates that the authors must not only address the conceptual and practical problems associated with this category but also reconcile it with the parallel medical descriptive classification of functional symptoms and syndromes. RESULTS: The existing somatoform disorders categories require modification. The authors favor the radical option of the abolition of the categories. Diagnoses currently within somatoform disorders could be redistributed into other groupings, and the disorders currently defined solely by somatic symptoms could be placed on axis III as "functional somatic symptoms and syndromes." Greater use could be made of "psychological factors affecting medical condition" on axis I. The authors suggest supplementing the diagnosis of functional somatic symptoms with a multiaxial formulation. CONCLUSIONS: The authors promote a classification of somatic symptoms in DSM-V that is compatible with that used in general medicine and offers new opportunities both for research into the etiology and treatment of symptoms and for the greater integration of psychiatry into general medical practice.